A polyaniline-zinc phosphate-aluminum tripolyphosphate composite water-based epoxy resin anticorrosive coating and preparation method thereof

By polymerizing polyaniline on the surface of zinc phosphate and aluminum tripolyphosphate, polyaniline-zinc phosphate-aluminum tripolyphosphate composite anticorrosion materials are formed, and the aqueous epoxy resin system is introduced, the insufficient performance of existing epoxy resin anticorrosion coatings in complex environments is solved, and higher mechanical properties and chemical corrosion resistance are achieved.

CN116948496BActive Publication Date: 2025-03-11GUANGXI RES INST OF NEW FUNCTIONAL MATERIALS CO LTD +2
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202311002328.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-10
Publication Date
2025-03-11
Estimated Expiration
2043-08-10

Smart Images

  • Figure BDA0004386717220000111
    Figure BDA0004386717220000111
Patent Text Reader

Abstract

The invention discloses a polyaniline zinc phosphate aluminum tripolyphosphate composite waterborne epoxy resin anticorrosive coating, comprising component A and component B, wherein the mass ratio of component A to component B is 5:(0.7-1.3); the component A comprises: 30-47 parts of epoxy resin, 10-25 parts of polyaniline zinc phosphate aluminum tripolyphosphate composite anticorrosive material, 3-10 parts of talc, 5-12 parts of barium sulfate, 2-11 parts of titanium dioxide, 1-2 parts of dispersant, 1-2 parts of defoamer, 1-5 parts of emulsifier, 1-4 parts of silane coupling agent, 1-6 parts of film-forming aid, 1-3 parts of leveling agent, 3-10 parts of other aids, and 3-11 parts of water; the component B comprises: 90-98 parts of epoxy resin curing agent, 1-5 parts of dispersant, and 1-5 parts of defoamer. The method for preparing the anticorrosive coating is as follows: mixing component A and component B in proportion and stirring evenly to obtain the anticorrosive coating. The invention can achieve the purpose of green environmental protection and enhance the mechanical properties and chemical corrosion resistance of the epoxy resin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of anti-corrosion coatings, and specifically relates to a polyaniline-zinc phosphate-aluminum tripolyphosphate composite water-based epoxy resin anti-corrosion coating and a preparation method thereof. Background Art

[0002] Epoxy resin anti-corrosion coatings have been widely used in the field of marine corrosion research due to their superior corrosion resistance, mechanical properties and strong adhesion. However, pure epoxy resin coatings have limited physical shielding capabilities, insufficient chemical corrosion resistance, single corrosion resistance, and insufficient coating hardness when facing complex environments, so it is difficult to meet actual needs. It can be seen that it is of great significance to develop an epoxy resin anti-corrosion coating with better performance. The introduction of two-dimensional materials into polymer resins is regarded as an effective strategy to improve the corrosion resistance of coating samples. At present, epoxy resin anti-corrosion coatings mainly include water-based epoxy resin anti-corrosion coatings and solvent-based epoxy resin anti-corrosion coatings. However, solvent-based epoxy resin anti-corrosion coatings are expensive, easy to cause environmental pollution, and endanger human health. With the improvement of people's environmental awareness, green and environmentally friendly water-based epoxy resin anti-corrosion coatings will become the trend of future industry development.

[0003] Polyaniline is a conductive polymer material. Its excellent chemical corrosion resistance and electrical conductivity make it an ideal material for improving epoxy resin anti-corrosion coatings. First, the anti-corrosion coating containing polyaniline can play a mechanical shielding role on the metal substrate material. Secondly, polyaniline has redox properties, which can promote the formation of a dense metal oxide layer at the junction of the coating and the metal substrate, thereby putting the metal in a passivated state, slowing down the corrosion rate of the metal, and effectively preventing the occurrence of corrosion. Polyaniline also has the advantages of good stability, non-toxic and environmentally friendly, scratch resistance, and pitting resistance. However, polyaniline also has its disadvantages as an anti-rust pigment, namely, low solubility, poor processability, and difficulty in dispersing and dissolving in aqueous media.

[0004] As an anti-rust pigment, zinc phosphate can react with the metal surface to form a dense phosphate film, thus playing an anti-rust role. In addition, it can also react with the carboxyl and hydroxyl groups in the base material and certain ions in the corrosive environment to form a protective film, which plays a corrosion inhibition role. Although zinc phosphate is a commonly used anti-rust pigment, it also has the disadvantages of insufficient anti-rust activity and slow formation of an effective protective film.

[0005] The excellent anti-rust ability of aluminum tripolyphosphate is mainly due to the anti-rust groups (P 3 O 10 5-), this group has strong coordination ability and activity, and can form a dense passivation film with metal ions, thereby effectively inhibiting metal corrosion. The pyrophosphate formed after the depolymerization of aluminum tripolyphosphate can be converted into orthophosphoric acid, reacting again with the surface of the substrate to form a more solid phosphating film, thus achieving "double rust prevention". In addition, the storage stability and weather resistance of aluminum tripolyphosphate are also excellent. Aluminum tripolyphosphate is a solid inorganic acid. Its application in coatings needs to pay attention to its compatibility with other raw materials to avoid adverse reactions that affect the anti-corrosion properties of the coating. In order to overcome this problem, it is usually necessary to modify or pigment aluminum polyphosphate to improve its stability and anti-corrosion properties in coatings.

[0006] The invention patent "A lignin sulfonate / polyaniline / poly(3,4-ethylenedioxythiophene) composite antistatic coating and its preparation and application", publication number: CN112266699A, discloses a method for preparing a lignin sulfonate / polyaniline / poly(3,4-ethylenedioxythiophene) composite antistatic coating. The invention first dissolves sodium lignin sulfonate in a hydrochloric acid aqueous solution, adds aniline and ammonium persulfate to react to obtain a lignin sulfonate / polyaniline nanocomposite, then adds ammonium persulfate to a mixed solution of the lignin sulfonate / polyaniline nanocomposite and 3,4-ethylenedioxythiophene to react to obtain a lignin sulfonate / polyaniline / poly(3,4-ethylenedioxythiophene) composite, and finally mixes lignin sulfonate / polyaniline / poly(3,4-ethylenedioxythiophene), epoxy resin and epoxy resin curing agent in a solvent to obtain an antistatic coating. The composite antistatic coating obtained by this method has low cost, is easy to use, and has good antistatic effect. However, the solvent used is organic solvents such as acetone, tetrahydrofuran, and xylene, which cause great pollution to the ecological environment and harm to construction workers, and the anti-corrosion effect is not obvious, which limits its application in industry.

[0007] The invention patent "A ship bottom anticorrosion coating and its preparation method", publication number: CN109517484A, discloses a ship bottom anticorrosion coating composed of two components A and B and its preparation method. Among them, group A is composed of water-based epoxy resin and deionized water, and group B is composed of epoxy curing agent, polyaniline, furfural resin, isocyanate, zinc phosphate, diacetone alcohol and graphite powder. The coating has excellent acid resistance, water resistance and salt spray resistance, which can meet the requirements of the ship bottom. However, the invention failed to effectively solve the problems of poor adhesion and poor dispersibility of the polyaniline component, and failed to give full play to the anticorrosion ability of polyaniline.

[0008] The above invention patents have failed to give full play to the anti-corrosion properties of polyaniline. In order to achieve better coating protection effects, and considering the respective advantages and disadvantages of polyaniline, zinc phosphate, and aluminum tripolyphosphate, polyaniline can be polymerized on the surface of zinc phosphate and aluminum tripolyphosphate to form a polyaniline-zinc phosphate-aluminum tripolyphosphate composite anti-corrosion material, and introduced into the epoxy resin system to form a good synergistic protection effect, thereby obtaining a green, environmentally friendly, and corrosion-resistant polyaniline-zinc phosphate-aluminum tripolyphosphate composite water-based epoxy resin anti-corrosion coating, which further optimizes the anti-corrosion performance, processing performance, and dispersion performance. Summary of the invention

[0009] In view of the above problems, the present invention provides a polyaniline-zinc phosphate-aluminum tripolyphosphate composite water-based epoxy resin anti-corrosion coating, which can achieve the purpose of green environmental protection and enhance the mechanical properties and chemical corrosion resistance of the epoxy resin.

[0010] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0011] A polyaniline-zinc phosphate-aluminum tripolyphosphate composite water-based epoxy resin anticorrosive coating, comprising a component A and a component B, wherein the mass ratio of the component A to the component B is 5:(0.7-1.3);

[0012] The component A comprises: 30-47 parts of epoxy resin, 10-25 parts of polyaniline-zinc phosphate-aluminum tripolyphosphate composite anticorrosive material, 3-10 parts of talc, 5-12 parts of barium sulfate, 2-11 parts of titanium dioxide, 1-2 parts of dispersant, 1-2 parts of defoamer, 1-5 parts of emulsifier, 1-4 parts of silane coupling agent, 1-6 parts of film-forming aid, 1-3 parts of leveling agent, 3-10 parts of other additives, and 3-11 parts of water;

[0013] The B component comprises: 90-98 parts of epoxy resin curing agent, 1-5 parts of dispersant, and 1-5 parts of defoaming agent.

[0014] Preferably, the epoxy resin is one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, polyphenol glycidyl ether epoxy resin, and glycidyl amine epoxy resin having an epoxy value of 41 to 54.

[0015] Preferably, the dispersant is one or more of polyacrylate sodium salt solution, polycarboxylate sodium salt solution, modified styrene maleic acid copolymer solution, modified polyether solution, Dow 731A, BYK-155, BYK-190, and BYK-192.

[0016] Preferably, the defoaming agent is one or more of concentrated silicone, polyether siloxane copolymer emulsion, silicone polymer emulsion, Dow Corning AFE-3168, TEGO-8030, TEGO-810, and BYK-A530.

[0017] Preferably, the emulsifier is one or more of modified polyurethane, polyoxyethylene octylphenol ether-10, Dow RM-12W, and Dow RM-8W.

[0018] Preferably, the silane coupling agent is one or more of 3-glycidyloxypropyltrimethoxysilane (KH-560), 3-(2,3-epoxypropyloxy)propyltriethoxysilane (KH-561), 3-mercaptopropyltriethoxysilane (KH-580), and 3-aminopropyltriethoxysilane (KH-550).

[0019] Preferably, the film-forming aid is one or more of lauryl alcohol ester, hexadecanol ester, propylene glycol phenyl ether, and propylene glycol butyl ether.

[0020] Preferably, the leveling agent is one or more of polyether-modified polydimethylsiloxane, fluorocarbon-modified polyacrylate, BYK-331, BYK-333, BYK-378, and BASF EFKA FL 3772.

[0021] Preferably, the other additives are one or more of iron red, manganese violet, iron blue, cobalt yellow, iron yellow, carbon black, manganese black, cobalt green, chrome green, and zinc white.

[0022] Preferably, the epoxy resin curing agent is one of polyamide, phenalkamine and modified polyamide.

[0023] Preferably, the preparation method of component A is: epoxy resin, dispersant, defoamer, emulsifier, water, polyaniline-zinc phosphate-aluminum tripolyphosphate composite anti-corrosion material, talcum powder, barium sulfate, titanium dioxide, silane coupling agent, film-forming aid, leveling agent, and other additives are added to a high-speed dispersion sand mill under low-speed stirring, followed by high-speed dispersion sand milling for 2 to 8 hours, sieving, and obtaining component A.

[0024] Preferably, the preparation method of component B is: adding epoxy resin curing agent, dispersant and defoaming agent into a high-speed dispersing sand mill respectively under low-speed stirring, then dispersing sand milling at high speed for 1 to 3 hours, sieving, and obtaining component B.

[0025] Preferably, the preparation method of the polyaniline-zinc phosphate-aluminum tripolyphosphate composite anti-corrosion material is as follows:

[0026] Step 1: Add water, zinc phosphate and aluminum tripolyphosphate into a sand mill and grind them thoroughly for 1 to 4 hours, and obtain a mixture powder by filtering, drying and crushing;

[0027] Step 2: Add aniline and the mixture powder in step 1 into water and stir well, add a pH adjuster, adjust the pH value to 1.5-3.5, and control the temperature to 2-10°C.

[0028] Step 3: Prepare the oxidant solution, add it dropwise into the dispersion of step 2, and fully react for 10 to 24 hours. After separation, washing and drying, a polyaniline-zinc phosphate-aluminum tripolyphosphate composite anti-corrosion material is obtained.

[0029] Preferably, in step 1, the mass ratio of zinc phosphate to aluminum tripolyphosphate is (1.2-2):1.

[0030] Preferably, in step 2, the mass ratio of aniline to the mixed powder in step 1 is (1-4):1.

[0031] Preferably, in step 2, the pH adjuster is one or more of phosphoric acid, phosphorous acid, phenylphosphonic acid, dibutyl phosphate, hydrochloric acid, sulfuric acid, glacial acetic acid, phytic acid, polymethacrylic acid, dodecylbenzenesulfonic acid, and sulfosalicylic acid.

[0032] Preferably, in step 3, the oxidant is one or more of hydrogen peroxide, sodium hypochlorite, hypochlorous acid, ammonium persulfate, potassium persulfate, potassium iodate, ferric chloride, potassium dichromate, potassium permanganate, and perchloric acid; and the added amount is 1 to 5 times the mass of aniline.

[0033] Preferably, the preparation method of the polyaniline-zinc phosphate-aluminum tripolyphosphate composite waterborne epoxy resin anticorrosion coating is: component A and component B are mixed and stirred evenly according to a proportion to obtain the polyaniline-zinc phosphate-aluminum tripolyphosphate composite waterborne epoxy resin anticorrosion coating.

[0034] Preferably, the polyaniline-zinc phosphate-aluminum tripolyphosphate composite water-based epoxy resin anti-corrosion coating is used by coating it on a pretreated metal surface and curing it at room temperature.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] 1. The present invention adopts the method of mechanical dispersion and chemical polymerization to polymerize polyaniline on the surface of zinc phosphate and aluminum tripolyphosphate to form a polyaniline-zinc phosphate-aluminum tripolyphosphate composite anticorrosion material. By combining organic polyaniline with inorganic zinc phosphate and aluminum tripolyphosphate, the problems of poor dispersibility and poor processability of polyaniline are improved, and the problem that zinc phosphate and aluminum tripolyphosphate are easy to absorb water and thus weaken the anticorrosion effect is optimized. At the same time, the three components cooperate with each other and establish an excellent metal protection barrier through different anticorrosion mechanisms. Due to the improvement in dispersibility, the polyaniline-zinc phosphate-aluminum tripolyphosphate composite anticorrosion material can be introduced into the waterborne epoxy resin system to prepare a polyaniline-zinc phosphate-aluminum tripolyphosphate composite waterborne epoxy resin anticorrosion coating, achieving the purpose of green environmental protection, while enhancing the mechanical properties and chemical corrosion resistance of the epoxy resin.

[0037] 2. The present invention mechanically grinds zinc phosphate and aluminum tripolyphosphate to form inorganic mixture particles with uniform particle size and uniform dispersion, and then coats the surface of the inorganic particles with polyaniline in an acidic environment to form a polyaniline-zinc phosphate-aluminum tripolyphosphate composite anticorrosion material. The generated polyaniline has good conductivity and can effectively exert its electrochemical anticorrosion ability, and the dopant anion therein also has corrosion inhibition effect. The polyaniline molecules are uniformly attached to the surface of the inorganic particles and are smoothly integrated into the water-based coating system through the interface effect of the inorganic particles, solving the problems of poor dispersibility and poor processability of polyaniline, and giving full play to the anticorrosion effect of polyaniline. As an organic molecule, polyaniline plays a physical shielding role on the inorganic particles of zinc phosphate and aluminum tripolyphosphate, effectively reducing the water absorption of the inorganic particles and improving the water resistance of the coating system.

[0038] 3. The present invention adopts polyaniline-zinc phosphate-aluminum tripolyphosphate composite anticorrosion material, and generates a dense metal oxide layer between the metal and the coating through the reversible redox characteristics of polyaniline itself, and at the same time cooperates with the phosphating film formed by zinc phosphate and metal, and the passivation film formed by the tripolyphosphate antirust group of aluminum tripolyphosphate and metal chelation, and the three cooperate to establish an excellent and long-lasting metal protection barrier. In addition, the polyaniline-zinc phosphate-aluminum tripolyphosphate composite anticorrosion material can also strengthen the adhesion between the coating and the metal, improve the weather resistance of the coating, and has the advantage of anti-scratch.

[0039] 4. The present invention introduces polyaniline-zinc phosphate-aluminum tripolyphosphate composite anti-corrosion material into the waterborne epoxy coating system, which further improves the chemical corrosion resistance and mechanical properties of the coating on the basis of the wear resistance, corrosion resistance and strong adhesion of the epoxy resin coating itself.

[0040] 5. The polyaniline-zinc phosphate-aluminum tripolyphosphate composite water-based epoxy resin anti-corrosion coating of the present invention adopts green and environmentally friendly materials with no side effects on human body and environment, does not use organic solvents such as xylene, n-butanol, benzyl alcohol, etc., reduces the emission of volatile organic compounds (VOCs), achieves environmental friendliness, and has simple process, convenient application and good stability. DETAILED DESCRIPTION

[0041] In order to facilitate a better understanding of the present invention, the following examples are used to illustrate the present invention. These examples belong to the protection scope of the present invention, but do not limit the protection scope of the present invention.

[0042] Example 1

[0043] A polyaniline-zinc phosphate-aluminum tripolyphosphate composite water-based epoxy resin anticorrosive coating, the preparation method of which comprises the following steps:

[0044] (1) Preparation of polyaniline-zinc phosphate-aluminum tripolyphosphate composite anticorrosion material: Add water, zinc phosphate, and aluminum tripolyphosphate into a sand mill to prepare a 20% dispersion and fully sand grind for 1 hour, wherein the mass ratio of zinc phosphate to aluminum tripolyphosphate is 1.2:1, and then filter, dry, and crush to obtain a mixture powder; add aniline and the mixture powder in a mass ratio of 4:1 into water and stir thoroughly, then add concentrated sulfuric acid, adjust the pH value to 1.5, and control the temperature to 2°C; then dissolve ammonium persulfate with a mass of 1 times that of aniline in a small amount of water, add dropwise to the above mixture solution, fully react for 24 hours, collect the solid by suction, and wash it twice with methanol and twice with water, and finally dry it at 80°C and crush it to obtain a polyaniline-zinc phosphate-aluminum tripolyphosphate composite anticorrosion material;

[0045] (2) Preparation of component A: 30 parts of bisphenol A epoxy resin with an epoxy value of 41, 2 parts of 731A dispersant, 1 part of Dow Corning AFE-3168 defoamer, 5 parts of RM-12W emulsifier, 4 parts of water, 25 parts of the above-mentioned polyaniline-zinc phosphate-aluminum tripolyphosphate composite anticorrosive material, 9 parts of talc, 5 parts of barium sulfate, 2 parts of titanium dioxide, 4 parts of KH-580 silane coupling agent, 6 parts of propylene glycol phenyl ether film-forming aid, 3 parts of BYK-331 leveling agent, and 4 parts of cobalt green were added to a high-speed dispersion sand mill under low-speed stirring at 500 r / min, followed by high-speed dispersion sand milling at 1500 r / min for 6 hours, and passed through a 300-mesh sieve to obtain component A;

[0046] (3) Preparation of component B: 98 parts of polyamide epoxy resin curing agent, 1 part of 731A dispersant, and 1 part of Dow Corning AFE-3168 defoamer were added to a high-speed dispersing sand mill under low-speed stirring at 500 r / min, followed by high-speed dispersing sand milling at 1000 r / min for 1 hour, and passed through a 300-mesh sieve to obtain component B;

[0047] (4) Preparation of polyaniline-zinc phosphate-aluminum tripolyphosphate composite water-based epoxy resin anti-corrosion coating: The above-mentioned component A and component B are mixed and stirred at a mass ratio of 5:1.3 for 10 minutes until they are in a uniform state, thereby obtaining a polyaniline-zinc phosphate-aluminum tripolyphosphate composite water-based epoxy resin anti-corrosion coating.

[0048] The polished tinplate was cleaned with acetone and ethanol and dried, and then the coating was evenly sprayed on the tinplate using an air spray gun and an air compressor, and then the coating was dried and cured at room temperature for 24 hours.

[0049] Example 2

[0050] A polyaniline-zinc phosphate-aluminum tripolyphosphate composite water-based epoxy resin anticorrosive coating, the preparation method of which comprises the following steps:

[0051] (1) Preparation of polyaniline-zinc phosphate-aluminum tripolyphosphate composite anticorrosion material: Add water, zinc phosphate, and aluminum tripolyphosphate into a sand mill to prepare a 20% dispersion and fully sand grind for 3 hours, wherein the mass ratio of zinc phosphate to aluminum tripolyphosphate is 1.4:1, and then filter, dry, and crush to obtain a mixture powder; add aniline and the mixture powder in a mass ratio of 2:1 into water and stir thoroughly, then add concentrated sulfuric acid, adjust the pH value to 2.8, and control the temperature to 5°C; then dissolve ammonium persulfate and potassium persulfate 5 times the mass of aniline in a small amount of water, add dropwise to the above mixture solution, fully react for 20 hours, collect the solid by suction, and wash it twice with methanol and twice with water, and finally dry it at 80°C and crush it to obtain a polyaniline-zinc phosphate-aluminum tripolyphosphate composite anticorrosion material;

[0052] (2) Preparation of component A: 40 parts of bisphenol A epoxy resin with an epoxy value of 51, 1 part of BYK-190 dispersant, 2 parts of TEGO-810 defoamer, 2 parts of RM-8W emulsifier, 11 parts of water, 16 parts of the above-mentioned polyaniline-zinc phosphate-aluminum tripolyphosphate composite anticorrosive material, 5 parts of talc, 7 parts of barium sulfate, 8 parts of titanium dioxide, 1 part of KH-561 silane coupling agent, 1 part of dodecyl ester film-forming aid, 1 part of BYK-333 leveling agent, and 5 parts of iron oxide red were added to a high-speed dispersion sand mill under low-speed stirring at 500 r / min, followed by high-speed dispersion sand milling at 1500 r / min for 6 hours, and passed through a 300-mesh sieve to obtain component A;

[0053] (3) Preparation of component B: 96 parts of phenolic amine epoxy resin curing agent, 2 parts of BYK-190 dispersant, and 2 parts of TEGO-810 defoamer were added to a high-speed dispersion sand mill under low-speed stirring at 500 r / min, followed by high-speed dispersion sand milling at 1000 r / min for 1 h, and passed through a 300-mesh sieve to obtain component B;

[0054] (4) Preparation of polyaniline-zinc phosphate-aluminum tripolyphosphate composite water-based epoxy resin anti-corrosion coating: The above-mentioned component A and component B are mixed and stirred at a mass ratio of 5:1.1 for 10 minutes until they are in a uniform state, thereby obtaining a polyaniline-zinc phosphate-aluminum tripolyphosphate composite water-based epoxy resin anti-corrosion coating.

[0055] The polished tinplate was cleaned with acetone and ethanol and dried, and then the coating was evenly sprayed on the tinplate using an air spray gun and an air compressor, and then the coating was dried and cured at room temperature for 24 hours.

[0056] Example 3

[0057] A polyaniline-zinc phosphate-aluminum tripolyphosphate composite water-based epoxy resin anticorrosive coating, the preparation method of which comprises the following steps:

[0058] (1) Preparation of polyaniline-zinc phosphate-aluminum tripolyphosphate composite anticorrosion material: Add water, zinc phosphate, and aluminum tripolyphosphate into a sand mill to prepare a 20% dispersion and fully sand grind for 4 hours, wherein the mass ratio of zinc phosphate to aluminum tripolyphosphate is 2:1, and then filter, dry, and crush to obtain a mixture powder; add aniline and the mixture powder in a mass ratio of 1:1 into water and stir thoroughly, then add 85% phosphoric acid, adjust the pH value to 3.5, and control the temperature to 10°C; then dissolve 3 times the mass of aniline in a little water, add dropwise to the above mixture solution, fully react for 10 hours, collect the solid by suction, and wash it twice with methanol and twice with water, and finally dry it at 80°C and crush it to obtain a polyaniline-zinc phosphate-aluminum tripolyphosphate composite anticorrosion material;

[0059] (2) Preparation of component A: 47 parts of bisphenol A epoxy resin with an epoxy value of 54, 1 part of BYK-155 dispersant, 1 part of BYK-A530 defoamer, 1 part of polyoxyethylene octylphenol ether-10 emulsifier, 7 parts of water, 10 parts of the above-mentioned polyaniline-zinc phosphate-aluminum tripolyphosphate composite anticorrosive material, 3 parts of talc, 9 parts of barium sulfate, 5 parts of titanium dioxide, 2 parts of KH-560 silane coupling agent, 3 parts of propylene glycol butyl ether film-forming aid, 2 parts of BYK-378 leveling agent, and 9 parts of cobalt yellow were added to a high-speed dispersion sand mill under low-speed stirring at 500 r / min, followed by high-speed dispersion sand milling at 1500 r / min for 6 hours, and passed through a 300-mesh sieve to obtain component A;

[0060] (3) Preparation of component B: 90 parts of modified polyamide epoxy resin curing agent, 5 parts of BYK-155 dispersant, and 5 parts of BYK-A530 defoamer were added to a high-speed dispersing sand mill under low-speed stirring at 500 r / min, followed by high-speed dispersing sand milling at 1000 r / min for 1 hour, and passed through a 300-mesh sieve to obtain component B;

[0061] (4) Preparation of polyaniline-zinc phosphate-aluminum tripolyphosphate composite water-based epoxy resin anti-corrosion coating: The above-mentioned component A and component B are mixed and stirred at a mass ratio of 5:0.7 for 10 minutes until they are uniform, thereby obtaining a polyaniline-zinc phosphate-aluminum tripolyphosphate composite water-based epoxy resin anti-corrosion coating.

[0062] The polished tinplate was cleaned with acetone and ethanol and dried, and then the coating was evenly sprayed on the tinplate using an air spray gun and an air compressor, and then the coating was dried and cured at room temperature for 24 hours.

[0063] Comparative Example 1

[0064] The water-based epoxy resin anticorrosive coating is prepared by using polyaniline synthesized by conventional emulsion polymerization, and the preparation method thereof comprises the following steps:

[0065] (1) Preparation of polyaniline: Aniline, OP-10, dodecylbenzene sulfonic acid and water were mixed into an emulsion in a mass ratio of 1:1:2:120 under stirring, and concentrated sulfuric acid was added to adjust the pH value to 2.8 and the temperature to 5°C. Ammonium persulfate and potassium persulfate (5 times the mass of aniline) were dissolved in a small amount of water and added dropwise to the emulsion to react for 20 hours. The solid was collected by filtration and washed twice with methanol and twice with water. Finally, it was dried at 80°C and crushed to obtain polyaniline.

[0066] (2) Preparation of component A: 40 parts of bisphenol A epoxy resin with an epoxy value of 51, 1 part of BYK-190 dispersant, 2 parts of TEGO-810 defoamer, 2 parts of RM-8W emulsifier, 11 parts of water, 4 parts of the above-mentioned polyaniline, 7 parts of zinc phosphate, 5 parts of aluminum tripolyphosphate, 5 parts of talc, 7 parts of barium sulfate, 8 parts of titanium dioxide, 1 part of KH-561 silane coupling agent, 1 part of dodecyl ester film-forming aid, 1 part of BYK-333 leveling agent, and 5 parts of iron oxide red were added to a high-speed dispersion sand mill under low-speed stirring at 500 r / min, followed by high-speed dispersion sand milling at 1500 r / min for 6 hours, and passed through a 300-mesh sieve to obtain component A;

[0067] (3) Preparation of component B: 96 parts of phenolic amine epoxy resin curing agent, 2 parts of BYK-190 dispersant, and 2 parts of TEGO-810 defoamer were added to a high-speed dispersing sand mill under low-speed stirring at 500 r / min, followed by high-speed dispersing sand milling at 1000 r / min for 1 hour, and passed through a 300-mesh sieve to obtain component B;

[0068] (4) Preparation of waterborne epoxy resin anticorrosion coating: The above-mentioned component A and component B are mixed and stirred at a mass ratio of 5:1.1 for 10 minutes until they are uniform, thereby obtaining a waterborne epoxy resin anticorrosion coating.

[0069] The polished tinplate was cleaned with acetone and ethanol and dried, and then the coating was evenly sprayed on the tinplate using an air spray gun and an air compressor, and then the coating was dried and cured at room temperature for 24 hours.

[0070] Comparative Example 2

[0071] Comparative Example 2 adopts the preparation method of Example 1 in the invention patent "A lignin sulfonic acid / polyaniline / poly(3,4-ethylenedioxythiophene) composite antistatic coating and its preparation and application" (Publication No.: CN112266699A) to prepare the coating.

[0072] The polished tinplate was cleaned with acetone and ethanol and dried, and then the coating was evenly sprayed on the tinplate using an air spray gun and an air compressor, and then the coating was dried and cured at room temperature for 24 hours.

[0073] Comparative Example 3

[0074] Comparative Example 3 adopts the preparation method of Example 1 in the invention patent "A ship bottom anti-corrosion coating and its preparation method" (publication number: CN109517484A) to prepare the coating.

[0075] The polished tinplate was cleaned with acetone and ethanol and dried, and then the coating was evenly sprayed on the tinplate using an air spray gun and an air compressor, and then the coating was dried and cured at room temperature for 24 hours.

[0076] Comparative Example 4

[0077] It is basically the same as Example 2, except that the polyaniline-zinc phosphate-aluminum tripolyphosphate composite anti-corrosion material is not added, and the preparation process steps of the polyaniline-zinc phosphate-aluminum tripolyphosphate composite anti-corrosion material are omitted accordingly.

[0078] Comparative Example 5

[0079] The method is basically the same as Example 2, except that the polyaniline-zinc phosphate-aluminum tripolyphosphate composite anti-corrosion material is replaced by polyaniline, and step (1) is a method for preparing polyaniline: aniline, OP-10, dodecylbenzene sulfonic acid and water are mixed into an emulsion in a mass ratio of 1:1:2:120 under stirring, and concentrated sulfuric acid is added to adjust the pH value to 2.8 and the temperature is controlled to 5°C; then ammonium persulfate and potassium persulfate with a mass of 5 times that of aniline are dissolved in a small amount of water and added dropwise to the emulsion, and the reaction is fully carried out for 20 hours. The solid is collected by suction, and washed twice with methanol and twice with water, and finally dried at 80°C and crushed to obtain polyaniline.

[0080] Comparative Example 6

[0081] It is basically the same as Example 2, except that the polyaniline-zinc phosphate-aluminum tripolyphosphate composite anti-corrosion material is replaced by zinc phosphate and applied directly.

[0082] Comparative Example 7

[0083] It is basically the same as Example 2, except that the polyaniline-zinc phosphate-aluminum tripolyphosphate composite anti-corrosion material is replaced by aluminum tripolyphosphate and directly used.

[0084] Performance test experiment

[0085] 1. Test the coating performance according to the following method:

[0086] 1. Observe the dispersion of the material in the coating with the naked eye. If the coating has no lumps and is in a uniform state, it is considered to be "well dispersed". The dispersion is divided into three categories: good dispersion, general dispersion and poor dispersion.

[0087] 2. Determine the surface drying time and actual drying time of the paint film according to "GB / T 1728-2020 Determination of Drying Time of Paint Film and Putty Film".

[0088] 3. Observe the appearance of the paint film with the naked eye. If the paint film has uniform color, is flat and smooth, and has no obvious sagging or bubbling, it is considered to have a "normal appearance". The paint film appearance is divided into normal and abnormal.

[0089] 4. The adhesion test of the coating is carried out according to GB / T 9286-2021 Paint and Varnish Cross-cut Test. It adopts a test method that cuts the coating with a right-angle grid pattern and penetrates to the substrate to evaluate the resistance of the coating to detach from the substrate. The test results are divided into 0 to 5 levels, with 0 being the best. For general purposes, 0 to 1 are satisfactory.

[0090] 5. Carry out salt spray resistance test of coating according to GB / T 1771-2007 Determination of neutral salt spray resistance of paints and varnishes to test the neutral salt spray resistance of coating.

[0091] 6. Test the water resistance of the coating according to "GB / T 1733-1993 Determination of water resistance of paint film" and use Method A (water immersion test method) to test the water resistance of the coating.

[0092] 2. The relevant performance data of the coatings prepared in Examples 1 to 3 and Comparative Examples 1 to 7 are shown in Table 1.

[0093] Table 1 Coating performance data of Examples 1 to 3 and Comparative Examples 1 to 7

[0094]

[0095] It can be seen from Table 1 that the polyaniline-zinc phosphate-aluminum tripolyphosphate composite water-based epoxy resin anti-corrosion coatings prepared in Examples 1 to 3 of the present invention have uniform components, are not easy to agglomerate, are well dispersed, have a surface drying time of less than 25 minutes, and a practical drying time of less than 8.5 hours. The prepared coating film is flat and smooth, has a normal appearance, and has an adhesion test of ≤1 level. The salt spray resistance can reach more than 1200 hours, and the water resistance can reach more than 1512 hours. Among them, the coating performance of Example 2 is better, with an adhesion level of 0, no abnormal salt spray resistance for 1416 hours, and no abnormal water resistance for 1632 hours, indicating that the polyaniline-zinc phosphate-aluminum tripolyphosphate composite water-based epoxy resin anti-corrosion coating described in the present invention has good dispersibility, and excellent adhesion, salt spray resistance, and water resistance.

[0096] In contrast, in Comparative Example 1, polyaniline synthesized by conventional emulsion polymerization was used to prepare the coating. The coating had more settled particles, some agglomerates, and general dispersibility. The prepared coating film had more particles, abnormal appearance, reduced adhesion, and relatively poor salt spray resistance and water resistance. This indicates that polyaniline synthesized by conventional emulsion polymerization is difficult to be evenly dispersed in water-based epoxy coatings, which affects the anti-corrosion performance of the coating.

[0097] Comparative Example 2 uses the coating of Example 1 in invention patent CN112266699A, and its salt spray resistance and water resistance are poor, indicating that its anti-corrosion performance is general.

[0098] Comparative Example 3 uses the coating of Example 1 in the invention patent CN109517484A, which has more settled particles and general dispersibility. The prepared coating film has more particles and abnormal appearance, and has poor salt spray resistance and water resistance, indicating that it fails to effectively solve the problem of poor dispersibility of the polyaniline component and fails to give full play to the anti-corrosion ability of polyaniline.

[0099] Comparative Example 4 does not add polyaniline-zinc phosphate-aluminum tripolyphosphate composite anti-corrosion material, and Comparative Examples 5 to 7 replace the polyaniline-zinc phosphate-aluminum tripolyphosphate composite anti-corrosion material with polyaniline, zinc phosphate, and aluminum tripolyphosphate, respectively. Among them, Comparative Example 4 does not add effective anti-corrosion pigments, resulting in poor anti-corrosion performance. Comparative Example 5 is affected by polyaniline and has more settled particles and general dispersibility, which reduces the anti-corrosion performance of the coating. Comparative Examples 6 to 7 only add a single anti-corrosion pigment, with limited anti-corrosion effect, and poor salt spray resistance and water resistance.

[0100] It can be seen that the polyaniline-zinc phosphate-aluminum tripolyphosphate composite water-based epoxy resin anti-corrosion coating described in the present invention has significant progress compared with the prior art, improves the dispersibility of polyaniline in the water-based epoxy resin anti-corrosion coating, and the three anti-corrosion materials of polyaniline, zinc phosphate and aluminum tripolyphosphate work synergistically and have excellent and long-lasting anti-corrosion performance.

[0101] The above description is only a preferred embodiment of the present invention and does not limit the present invention. For those skilled in the art, the present invention may have various modifications and changes. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A polyaniline-zinc phosphate-aluminum tripolyphosphate composite waterborne epoxy resin anticorrosive coating, characterized in that: It comprises component A and component B, wherein the mass ratio of component A to component B is 5:(0.7-1.3); The component A comprises: 30-47 parts of epoxy resin, 10-25 parts of polyaniline-zinc phosphate-aluminum tripolyphosphate composite anticorrosive material, 3-10 parts of talc, 5-12 parts of barium sulfate, 2-11 parts of titanium dioxide, 1-2 parts of dispersant, 1-2 parts of defoamer, 1-5 parts of emulsifier, 1-4 parts of silane coupling agent, 1-6 parts of film-forming aid, 1-3 parts of leveling agent, 3-10 parts of other additives, and 3-11 parts of water; The B component includes: 90-98 parts of epoxy resin curing agent, 1-5 parts of dispersant, and 1-5 parts of defoaming agent; the preparation method of the polyaniline-zinc phosphate-aluminum tripolyphosphate composite anticorrosive material is as follows: Step 1: Add water, zinc phosphate and aluminum tripolyphosphate into a sand mill and grind them thoroughly for 1 to 4 hours, and obtain a mixture powder by filtering, drying and crushing; Step 2: Add aniline and the mixture powder in step 1 into water and stir thoroughly, add a pH adjuster, adjust the pH value to 1.5-3.5, and control the temperature to 2-10°C; Step 3: Prepare the oxidant solution, add it dropwise into the dispersion of step 2, and fully react for 10 to 24 hours. After separation, washing and drying, a polyaniline-zinc phosphate-aluminum tripolyphosphate composite anti-corrosion material is obtained.

2. The polyaniline-zinc phosphate-aluminum tripolyphosphate composite waterborne epoxy resin anticorrosive coating according to claim 1, characterized in that: The epoxy resin is one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, polyphenol glycidyl ether epoxy resin, and glycidyl amine epoxy resin having an epoxy value of 0.41 to 0.54; The dispersant is one or more of polyacrylate sodium salt solution, polycarboxylate sodium salt solution, modified styrene maleic acid copolymer solution, modified polyether solution, Dow 731A, BYK-155, BYK-190, and BYK-192; The defoaming agent is one or more of concentrated silicone, polyether siloxane copolymer emulsion, silicone polymer emulsion, Dow Corning AFE-3168, TEGO-8030, TEGO-810, and BYK-A530; The emulsifier is one or more of modified polyurethane, polyoxyethylene octylphenol ether-10, Dow RM-12W, and Dow RM-8W; The silane coupling agent is one or more of 3-glycidyloxypropyltrimethoxysilane (KH-560), 3-(2,3-epoxypropyloxy)propyltriethoxysilane (KH-561), 3-mercaptopropyltriethoxysilane (KH-580), and 3-aminopropyltriethoxysilane (KH-550); The film-forming aid is one or more of lauryl alcohol ester, hexadecanol ester, propylene glycol phenyl ether, and propylene glycol butyl ether; the leveling agent is one or more of polyether-modified polydimethylsiloxane, fluorocarbon-modified polyacrylate, BYK-331, BYK-333, BYK-378, and BASF EFKAFL 3772; The other additives are one or more of iron red, manganese violet, iron blue, cobalt yellow, iron yellow, carbon black, manganese black, cobalt green, chrome green, and zinc white; The epoxy resin curing agent is one or more of polyamide, phenolic amine and modified polyamide.

3. The polyaniline-zinc phosphate-aluminum tripolyphosphate composite waterborne epoxy resin anticorrosive coating according to claim 1, characterized in that: The preparation method of component A is as follows: epoxy resin, dispersant, defoamer, emulsifier, water, polyaniline-zinc phosphate-aluminum tripolyphosphate composite anti-corrosion material, talcum powder, barium sulfate, titanium dioxide, silane coupling agent, film-forming aid, leveling agent and other additives are added into a high-speed dispersion sand mill under low-speed stirring, followed by high-speed dispersion sand milling for 2 to 8 hours, sieving, and obtaining component A.

4. The polyaniline-zinc phosphate-aluminum tripolyphosphate composite waterborne epoxy resin anticorrosive coating according to claim 1, characterized in that: The preparation method of component B is as follows: epoxy resin curing agent, dispersant and defoamer are added into a high-speed dispersing sand mill respectively under low-speed stirring, followed by high-speed dispersing sand milling for 1 to 3 hours, and sieving to obtain component B.

5. The polyaniline-zinc phosphate-aluminum tripolyphosphate composite waterborne epoxy resin anticorrosive coating according to claim 1, characterized in that: In step 1, the mass ratio of zinc phosphate to aluminum tripolyphosphate is (1.2-2):

1.

6. The polyaniline-zinc phosphate-aluminum tripolyphosphate composite waterborne epoxy resin anticorrosive coating according to claim 1, characterized in that: In step 2, the mass ratio of aniline to the mixed powder in step 1 is (1-4):

1.

7. The polyaniline-zinc phosphate-aluminum tripolyphosphate composite waterborne epoxy resin anticorrosive coating according to claim 1, characterized in that: In step 2, the pH adjuster is one or more of phosphoric acid, phosphorous acid, phenylphosphonic acid, dibutyl phosphate, hydrochloric acid, sulfuric acid, glacial acetic acid, phytic acid, polymethacrylic acid, dodecylbenzenesulfonic acid, and sulfosalicylic acid.

8. The polyaniline-zinc phosphate-aluminum tripolyphosphate composite waterborne epoxy resin anticorrosive coating according to claim 1, characterized in that: In step 3, the oxidant is one or more of hydrogen peroxide, sodium hypochlorite, hypochlorous acid, ammonium persulfate, potassium persulfate, potassium iodate, ferric chloride, potassium dichromate, potassium permanganate, and perchloric acid; and the mass thereof is 1 to 5 times the mass of aniline.

9. A method for preparing the polyaniline-zinc phosphate-aluminum tripolyphosphate composite waterborne epoxy resin anticorrosive coating according to any one of claims 1 to 8, characterized in that: The component A and the component B are mixed and stirred evenly according to a certain proportion to obtain a polyaniline-zinc phosphate-aluminum tripolyphosphate composite water-based epoxy resin anti-corrosion coating.

Citation Information

Patent Citations

  • Bottom-layer anticorrosion coating for ships and preparation method of bottom-layer anticorrosion coating

    CN109517484A

  • Lignosulfonic acid / polyaniline / poly(3,4-ethylenedioxythiophene) composite antistatic coating as well as preparation and application thereof

    CN112266699A

  • Aluminum-tripolyphosphate-doped polyaniline antirust pigment and preparation method thereof

    CN102226045A

  • Modified environmentally-friendly heavy duty anticorrosion coating and preparation method thereof

    CN105419565A

  • Waterborne polyaniline anticorrosive coating and preparation method thereof

    CN108753116A